Evaluadores del Volumen 36(2) - ., Runa (RUNA, archivo para las ciencias del hombre, 2015)
Evaluadores Nacionales Carolina Alvarez Avila – Universidad Nacional de Córdoba Silvia Balzano – Pontificia Universidad Católica Argentina Natalia Castelnuovo – Universidad Nacional de San Martín Andrés Dapuez – Universidad Nacional de Entre Ríos Mariano Carlos Del Papa – Universidad Nacional de La Plata María Laura Diez – Universidad de Buenos Aires Mariana Fabra – Universidad Nacional de Córdoba Claudia Figari – CEIL - CONICET Valeria Hernández – Universidad Nacional de San Matrín Carina Jofre – Universidad Nacional de San Juan Mario Lattuada – Universidad Nacional de Rosario Mariana Lorenzetti – Universidad de Buenos Aires María Inés Poduje – Universidad Nacional de La Pampa Pablo Schamber – Universidad Nacional de Lanús Héctor Vázquez – Universidad Nacional de Rosario Areli Veloz Contreras – Universidad Nacional de San Matrín Evaluadores Extranjeros Jean Pierre Bastian – Universidad Marc Bloch Estrasburgo, Francia Alinne Bonetti – Universidad Federal do Pampa (Unipampa), Brasil Luis Cayòn – Universidad de Brasilia, Brasil Jean Langdon – Universidad Federal de Santa Catarina, Brasil María Clara Medina – Universidad de Göterborg, Suecia Diana Mulinari – Lund University, Suecia Flávio Braune Wiik – Universidad Estadual de Londrina, Brasil